The Effect of Market Orientation on a Company’s Performance - Dikčius, Vytautas (Ekonomika, 2002)
The article focuses on one of the business philosophies - market orientation, and its relationship to a company’s performance. For this purpose, two questionnaires for market orientation measurement were developed (one adopted from Kohli and Jaworski, another - from Deng and Dart) and their reliability and validity were evaluated. Also analysed and evaluated were the relationship between the level of market orientation in a company and the subjective evaluation of a company’s performance - the overall financial situation of the company. its financial situation in 1998 as compared to 1997, financial situation of the company compared to the situation in the industry. and the financial situation of the company compared to its competitors. The research was performed among Lithuanian furniture manufacturing companies.